Putusan Hakim Terkait Bukti Tidak Langsung (Circumstantial Evidence) Pada Kasus Pembunuhan Berencana (Studi Putusan Pengadilan Jakarta Pusat Nomor 777/Pid.B/2016/Pn Jkt.Pst) - I Made Minggu Widyantara; Ivony Stefania Seran Tahuk; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2025)
Crime is the entirety of human behavior including conduct and behavior that is against the law and should be punished as outlined in a form of legislation. Premeditated murder is classified as a criminal offense and should be punished. In Decision Number 777/Pid.B/2016/PN JKT.PST, a case of premeditated murder was proven and Jessica Kumala Wongso was the defendant. When convicting a prisoner, judges use circumstantial evidence. This research seeks to define circumstantial evidence in Decision Number 777/Pid.B/2016/PN JKT.PST. How does the court defend the conclusion of circumstantial evidence in Decision Number 777/Pid.B/2016/PN JKT.PST? This research uses normative legal research. Decision Number 777/Pid.B/2016/PN JKT. PST is based on the judge's assessment of the results of the formulation of the problem and conclusions as well as indirect evidence or circumstantial evidence.